Circulating monocyte populations as biomarker for abdominal aortic aneurysms: a single-center retrospective cohort study - Klopf, Johannes; Zagrapan, Branislav; Brandau, Annika; Lechenauer, Peter; Candussi, Catharina J.; Rossi, Patrick; Celem, Nihan Dide; Ziegler, Michael; Fuchs, Lukas; Hayden, Hubert; Krenn, Claus G.; Eilenberg, Wolf; et al. (Frontiers in Immunology, 2024)
Background Abdominal aortic aneurysm (AAA) development is driven by inflammation, in particular myeloid cells, which represent attractive biomarker candidates. Yet to date, the maximum aortic diameter is the only clinically applied predictor of AAA progression and indicator for surgical repair. We postulated that aortic inflammation is reflected in a systemic change of monocyte populations, which we investigated regarding marker potential in AAA diagnosis and prognosis. Methods We conducted a single-center retrospective cohort study in a diagnostic setting, measuring monocyte subsets by flow cytometry in peripheral blood samples of 47 AAA patients under surveillance, matched with 25 healthy controls and 25 patients with peripheral artery disease (PAD). In a prognostic setting, we acquired longitudinal data of 60 AAA patients including aneurysm growth assessment by computed tomography at 6-month intervals. Results Blood levels of total monocytes, CD16+ monocytes and particularly intermediate monocytes were significantly increased in AAA patients versus healthy individuals and were also elevated compared to PAD patients. The combination of intermediate monocyte and D-dimer blood levels outperformed the individual diagnostic marker values. Additionally, the elevated concentrations of total monocytes, intermediate monocytes, and monocyte-platelet aggregates (MPA) were suited to predict rapid AAA progression over short-term periods of six months. Of note, MPA were identified as independent predictor of AAA disease progression in multivariable analysis. Conclusion Circulating monocyte subsets are elevated in AAA patients and support diagnosis and prediction of aneurysm progression. Monocyte subsets and D-dimer reflect different hallmarks (inflammation and hemostasis) of AAA pathology and when combined, may serve as improved biomarker.